Avaliação do teste de imunoperoxidase para detecção de anticorpos contra o vírus da leucose bovina (BLV) - Castro, Clarissa Caetano de (2011)
The enzootic bovine leukosis is an illness caused by the bovine leukosis virus (BLV) which provokes a persistent infection in cattle and is responsible for significant economical losses to the bovines, mainly dairy cattle. It is widely spread in Brazilian cattle and it can come up in three forms: asymptomatic infection, persistent lymphocytosis and lymphosarcoma. The animals that have antibodies against the BLV must be eliminated or separated from the rest of the cattle, because they are carriers and disseminators of the virus during all their lifetimes. The diagnosis of this disease is essential for control and eradication strategies based on the segregation of infected animals in order to avoid or attenuate the transmission of the virus, and consequently, minimize the economical losses caused by the disease. During the BLV infection antibodies are produced against the main viral proteins, gp 51, gp 30 (envelope glicoproteins) and p24 (capsid protein). The agar gel immunodiffusion (AGID) and the enzyme-linked immunosorbent assay (ELISA) tests are the most used for diagnosis. In this report the immunoperoxidase technique (peroxidase linked assay - PLA) was evaluated in order to detect antibodies against the BLV. The results obtained in the PLA were compared with the AGID test and the specificity of the positive ones was confirmed by the Western blotting (WB) technique. Two hundred and one bovine serum samples of cattle coming from the city of Pelotas were tested: 59% (119) were positive in PLA and 26% (53) were positive in AGID. All the AGID positive samples were also PLA positive. From the 32,8% (66) of the conflicting serum results just eight were confirmed as positive in WB, indicating that the rest of the results were false-positive and showing that AGID failed in identifying 4% of the BLV positive animals. The PLA technique for the diagnosis of the BLV infection demonstrated to be very useful to use in control programs because it was more sensitive when compared to the AGID technique. However, the occurrence of false-positive results by the PLA makes its use unviable in eradication programs that involve the sacrifice of seropositive animals.